Empowering Chinese Young Female Fans on Social Media through Artificial Intelligence to Control their Body Image - Fan, Xiaoyu (Oxbridge Publishing House, 2024)
The purpose of this qualitative study was to empower the young Chinese fans on social media through artificial intelligence (as virtual influencers) to control their body image. The study aimed to investigate fans' opinions, experiences, and obstacles in relation to body image perception, acceptance and satisfaction through in-depth interviews with 21 informants. Based on the interview questions and research aims and objectives, a total of 11 themes were formulated to perform the thematic analysis. According to the findings, fan involvement, social media use, and exposure to idealized body ideals of virtual influencers had an impact on body image perceptions and among Chinese young female fans. The findings also highlighted the relevance of social support and positive fan groups in fostering body image satisfaction. This study's theoretical and practical implications add to the current literature by shedding light on the complex interplay between virtual celebrity, fan practices, social media and body image satisfaction. The study emphasizes the importance of focused interventions and support networks that meet the specific issues that Chinese young female fans experience in maintaining the confidence for embracing healthy body image. The study's weaknesses and future research directions are also discussed.